STRATEGI MARKETING PUBLIC RELATIONS HAUS INDONESIA DALAM MEMPERTAHANKAN CORPORATE IMAGE - Yuningsih, Siska (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
This study aims to analyze the marketing public relations strategy implemented by Haus! Indonesia is maintaining its corporate image as a modern beverage brand focused on the millennial generation. Using a qualitative approach with descriptive analysis methods, data collection techniques through interviews, observations and literature studies. The theory used is from the Three Ways Strategy concept by Thomas L. Harris, namely push strategy, pull strategy, and pass strategy. The results of the study show that Haus! Indonesia implements a marketing public relations strategy based on the Three Ways Strategy concept by Thomas L. Harris, namely push strategy (direct promotion), pull strategy (interactive digital communication), and pass strategy (social activities and CSR). These three strategies are carried out synergistically by the central team and field implementers to build a positive, adaptive, and relevant brand image. The marketing public relations strategy has been proven to have a real impact on increasing consumer engagement and maintaining the company's image amidst the competition in the contemporary beverage industry. Keywords: Marketing Public Relations, Three Ways Strategy, Corporate Image